INTERLEUKIN-6 YANG TINGGI SEBAGAI FAKTOR RISIKO TERHADAP KEJADIAN OSTEOPOROSIS PADA WANITA PASCAMENOPAUSE DEFISIENSI ESTROGEN - Kawiyana, Siki (journal of internal medicine, 2012)
In estrogen deficient post-menopausal women, the decrease of estrogen level in blood is not the sole cause for osteoporosis. Osteoporosis occurs due to the increase of osteoclastic bone resorption activity. OsteoclastÕs number and activity depend on its activating factors such as interleukine-6 (IL-6). The aim of the study was to prove that high IL-6 serum concentration is a risk factor for osteoporosis. The study was an analytic-observational study in case-control design, which was done at Sanglah General Hospital, Denpasar. The sample size was 41 case subjects (osteoporosis) and 41 control subjects (non-osteoporosis) using paired case-control sample size formula. The t-paired and McNemartestsresults were: (1). IL-6 concentration was higher significantly in case compared than control (3.47 ± 1.75 pg/mL vs 2.51 ± 1.13 pg/mL, p=0.001). (2). As risk factor for osteoporosis, using 2.17 pg/ml as the cut off point, the IL-6 has significant OR as high as 4 (CI 95%: 1.23 Ð 14.24, p=0.032). From this study we may derive conclusions as follows: (1). In estrogen deficient post-menopausal women, IL-6 concentration was higher in osteoporosis than non-osteoporosis. (2). The high IL-6 serum concentration was a risk factor for osteoporosis in estrogen deficient postmenopausal women. (3). High IL-6 serum concentration can be used as predictor for osteoporosis in estrogen deficient postmenopausal women
Keywords: post-menopausal osteoporosis, estrogen, interleukine-6